Transmission path optimization Based on Efficiency Communication System - Jin Fan; Kit, Guan Lim; Sin, Helen Ee Chuo; Min, Keng Tan; Ali Farzamnia; Tze, Kenneth Kin Teo (2022)
Routing is the core of wireless sensor network deployment. This paper points out the research focus of the wireless sensor network transmission path and discusses the optimization problem of the transmission based on grid model. In this paper, routing attribute table that is maintained by the nodes, the density and relative distance of node distribution, is used to determine the clustering method. At the same time, the developed algorithm combines the relative position of the cluster and the base station to further improve the routing method of the sub-cluster head, Finally, the algorithm analyzes the influence of different parameters on the transmission path, and use the simulation experiments to evaluate the conclusions.